2014
DOI: 10.1097/mlr.0000000000000134
|View full text |Cite
|
Sign up to set email alerts
|

Will Health Care Reform Reduce Disparities in Insurance Coverage?

Abstract: The dependent coverage mandate of the Affordable Care Act increased insurance rates among all racial and ethnic groups but did not change overall disparities. Disparities may have widened among low-income populations which highlights the importance of Medicaid expansions in reducing disparities. Among higher-income populations, disparities between non-Hispanic blacks and non-Hispanic whites were reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 5 publications
2
40
0
Order By: Relevance
“…To reduce health disparities in vulnerable populations, the present study highlights the need to develop multilingual measurement tools. [27][28][29]31 Secondary findings that support the potential applications of tablet-based PROM approaches were also observed in the present study. Specifically, associations were found between PROMIS-10 scores and mRS scores in stroke patients and between PROMIS-10 and QOLIE scores in patients with epilepsy.…”
Section: Figuresupporting
confidence: 71%
See 2 more Smart Citations
“…To reduce health disparities in vulnerable populations, the present study highlights the need to develop multilingual measurement tools. [27][28][29]31 Secondary findings that support the potential applications of tablet-based PROM approaches were also observed in the present study. Specifically, associations were found between PROMIS-10 scores and mRS scores in stroke patients and between PROMIS-10 and QOLIE scores in patients with epilepsy.…”
Section: Figuresupporting
confidence: 71%
“…15,25 However, delivery models described in the literature contain substantial methodological differences, including various clinical settings, patient characteristics collected, and survey technologies. 15,17,[26][27][28][29] Many cases fail to report participation rate. 17,30 A prior study demonstrates the collection of patient-reported outcomes (i.e., PROMIS physical functional scale) at an academic cerebrovascular clinic using an electronic platform over a time frame of 33 months, reaching 1,946 stroke patients.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…4 Several studies have supported the finding that the new law has decreased the number of uninsured young adults by increasing the prevalence of private insurance coverage. [5][6][7][8][9][10] The uninsured rate for this age group is projected to continue to fall with implementation of state Medicaid expansions and insurance exchanges. 5 Uninsured young adults encounter barriers when accessing other health care services, such as being unable to afford prescription drugs.…”
Section: Introductionmentioning
confidence: 99%
“…One perspective is that the ACA will have the paradoxical effect of increasing health disparities across states, particularly among racial minorities [4]. Initial evaluations of the health insurance uptake since the ACA substantiate this claim [5]. …”
Section: Introductionmentioning
confidence: 99%